2014
DOI: 10.1039/c4ta04605f
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconfinement of phase change materials within carbon aerogels: phase transition behaviours and photo-to-thermal energy storage

Abstract: We systematically investigated the thermal energy storage properties and host-guest interactions in a phase change composite based on octadecanol/carbon aerogels. Due to the nanoconfinement effect induced by the carbon aerogels, the loaded active materials show distinct phase transition behaviour to the free octadecanol, in which the solid-to-solid and solid-to-liquid phase change processes occurred at a lower temperature and the interval between these two processes became larger. † Electronic supplementary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(67 citation statements)
references
References 63 publications
3
64
0
Order By: Relevance
“…The thermal conductivities of organic PCMs and salt hydrates range from ≈0.1 to 1 W m −1 K −1 , and those of inorganic salts range from ≈0.5 to 5 W m −1 K −1 . [26] There are generally two approaches to tuning k PCM : filling additives [29] or encapsulating into porous matrixes or shells [30] with high thermal conductivities. Extensive available reviews related to the thermal conductivity enhancement of PCMs have been reported, which summarized the strategies for improving thermal conductivities in detail.…”
Section: Thermal Conductivity Enhancement Of Pcmsmentioning
confidence: 99%
“…The thermal conductivities of organic PCMs and salt hydrates range from ≈0.1 to 1 W m −1 K −1 , and those of inorganic salts range from ≈0.5 to 5 W m −1 K −1 . [26] There are generally two approaches to tuning k PCM : filling additives [29] or encapsulating into porous matrixes or shells [30] with high thermal conductivities. Extensive available reviews related to the thermal conductivity enhancement of PCMs have been reported, which summarized the strategies for improving thermal conductivities in detail.…”
Section: Thermal Conductivity Enhancement Of Pcmsmentioning
confidence: 99%
“…However, these efforts would certainly lessen the energy storage density of PCMs due to the presence of inactive mass . At present, nanoconfinement technologies have attracted a lot of interest and present a new opportunity for considerable refinement in the thermophysical properties of PCMs while sustaining their energy storage capacity . There are several advantages associated with nanoconfinement like small domain size, large surface area, diverse surface functionalities, controlled volume expansion, reduced reactivity with the external environment, and high heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have been testied that the phase change temperatures of organic phase change materials decrease as the supporting spaces become narrower. 45,50,51 Thus, the SA molecules adsorbed in serial narrower pore exhibited different lower temperature of phase change just like SA/SG 1 and SA/SG 5 (Fig. 5a).…”
Section: -49mentioning
confidence: 99%
“…It resulted in the phase change temperatures further shied to lower temperature due to the rotation of the hydrocarbon chains require more low thermal energy in this condition. 50,51 Compared with the pore size distribution in incremental pore volume of the SG 1 and SG 5 (20-60 nm and 40 nm), the SG 10 had a smaller and concentrated size range (5-30 nm and 25 nm), generating a dened phase change peaks occurring 10 C lower. Also, the interaction (including surface tension forces and capillary forces) occurred between the SA and the SG matrix would be strong enough to disturb its phase change process when the pore can conne the crystallization of the PCM.…”
Section: -49mentioning
confidence: 99%